Interview with Dr. Juan José Marín. Experiences in the Historical Study of the Prostitution in Costa Rica - Orozco Varela, Luis Pablo (2020)
This interview constitutes an unpublished material that refers to the work of the historian Juan José Marín Hernández (Q.E.D.P), regarding his career in the investigation of prostitution history in Costa Rica. The interview was conducted in February 2015 and was also a look of Marin around the recent history of Costa Rica, through which he analyzed issues such as neoliberalism, the rise of tourism, exclusion, inequalities, the Public morals, among others. His work is linked to sources and authors, some of whom were retaken in the content of this dialogue.